The effect of temperature and feed intake on growth rate of tinfoil barb (Barbonymus schwanenfeldii) - Joshua Ilau. (Universiti Putra Malaysia, 2016)
This experiment aimed to investigate the effects of temperature (30°C and 34 °C ) on feed intake and growth performance of B. Schwanenfeldii. A total of 48 fish with 18 cm(average size) were randomly stocked in eight 25L aquarium tank(8 fish per tank). Four tanks were held at a temperature 30 °C ± 29 °C while the other four tanks were held at 34° C ± 33 °C. Fish were fed twice a day with 40% of body weight for 56 days. The growth and growth efficiency data were analysed using independent two samples t – test and all results showed that the differences on fish when cultured in two different temperatures. Results indicated that fish cultured at 34°C had better growth and growth efficiency compared to 30°C. Thus, increasing the temperature would not give an adverse effects on growth performance and effieciency of B.schwanenfeldii juvenile.